STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KECERDASAN SPIRITUAL SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI 30 SAROLANGUN - Asriyani; Lubis, Ali Musa; Hasanah, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of participation of ninth-grade students in religious value development activities at State Junior High School 30 Sarolangun Regency indicates problems in fostering students’ spiritual intelligence. This condition is influenced by various factors, both internal, such as students’ motivation and religious awareness, and external factors, including family, school, and community environments. Therefore, the strategic role of Islamic Religious Education teachers is crucial in designing and implementing learning and guidance strategies that can effectively enhance students’ spiritual intelligence. This study aims to describe and analyze the strategies employed by Islamic Religious Education teachers in improving students’ spiritual intelligence at State Junior High School 30 Sarolangun Regency, as well as to identify supporting and inhibiting factors in their implementation. This research adopts a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation. The findings reveal that Islamic Religious Education teachers apply various strategies, such as habituation of worship practices, role modeling, integration of spiritual values into classroom learning, and religious extracurricular activities. These strategies contribute to improving students’ religious awareness and spiritual intelligence, although several obstacles remain, including limited environmental support and inadequate facilities. This study is expected to serve as a reference for schools, teachers, and stakeholders in enhancing the quality of students’ spiritual development